Using knowledge of, attitude toward, and daily preventive practices for COVID-19 to predict the level of post-traumatic stress and vaccine acceptance among adults in Hong Kong - Cao, Yuan; Siu, Judy Yuen-man; Choi, Kup-Sze; Ho, Nick Cho-lik; Wong, Kai Chun; Shum, David H. K. (Frontiers in Psychology, 2022)
Introduction COVID-19 has been perceived as an event triggering a new type of post-traumatic stress (PTSD) that can live during and after the pandemic itself. However, it remains unclear whether such PTSD is partly related to people’s knowledge of, attitude toward and daily behavioral practices (KAP) for COVID-19. Methods Through a telephone survey, we collected responses from 3,011 adult Hong Kong residents. Then using the Catboost machine learning method, we examined whether KAP predicted the participant’s PTSD level, vaccine acceptance and participation in voluntary testing. Results Results suggested that having good preventative practices for, poor knowledge of, and negative attitude toward COVID-19 were associated with greater susceptibility to PTSD. Having a positive attitude and good compliance with preventative practices significantly predicted willingness to get vaccinated and participate in voluntary testing. Good knowledge of COVID-19 predicted engagement in testing but showed little association with vaccine acceptance. Discussion To maintain good mental health and ongoing vaccine acceptance, it is important to foster people’s sense of trust and belief in health professionals’ and government’s ability to control COVID-19, in addition to strengthening people’s knowledge of and compliance with preventative measures.